The Impact of Kahoot-Based Media on Learning Motivation in the Topic of Periodic Properties of Elements - Bahriah, Evi Sapinatul; Larataqiy, Cyrilla (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
The purpose of this study was to determine the implementation of Kahoot media on learning motivation on periodic properties of elements based on learning motivation indicators. This type of research is descriptive quantitative with purposive sampling technique on 36 students of class X-B SMAN Bogor Regency which was conducted in October 2024. The data collection technique used was a questionnaire. The results of this study indicate an increase in learning motivation with an average percentage value of 77.66 (good category). So it can be concluded that Kahoot media can increase students' learning motivation on Periodic Properties of Elements material based on learning motivation indicators.